Finite Element Analysis and Structural Design of Vehicular Manipulator. Issue 4 (May 2019) - Gan, Yong; Zhang, Qiufeng; Meng, Xu; Wen, Yongsen; Zhu, Weiqiang
Abstract: Based on the requirement of flexible operation of intelligent car in narrow welding environment, a vehicle-mounted manipulator which is capable of carrying spray gun was designed. In order to make the manipulator have reasonable structure and dynamic characteristics, SolidWorks software is used to carry out three-dimensional modeling, static stress analysis and modal analysis of the vehicle-mounted manipulator. Based on the experimental data, it is concluded that the end of the manipulator is easy to be destroyed, At the same the optimization design of the arm is carried out, such as lightweight, reinforcement of the load-bearing part and so on. The experimental results show that the maximum stress of the load-bearing parts is reduced by about 34.26% after optimization, while the maximum stress of the arm is reduced by 30.3% after optimization, and the mass is reduced by 53.3%. The performance is improved obviously, which provides a theoretical basis for the manufacture of intelligent car platform with thermal stress relief at weld joint.